2013
DOI: 10.1111/jipb.12021
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Genetic Analysis of a Novel Rice Spotted‐leaf Mutant HM47 with Broad‐spectrum Resistance to Xanthomonas oryzae pv. oryzae

Abstract: A stable inherited rice spotted-leaf mutant HM47 derived from an EMS-induced IR64 mutant bank was identified. The mutant expressed hypersensitive response (HR)-like symptoms throughout its whole life from the first leaf to the flag leaf, without pathogen invasion. Initiation of the lesions was induced by light under natural summer field conditions. Expression of pathogenesis-related genes including PAL, PO-C1, POX22.3 and PBZ1 was enhanced significantly in association with cell death and accumulation of H 2 O … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 56 publications
0
41
0
Order By: Relevance
“…We believe that the identification of the rice lmr mutant and isolation of the corresponding LMR gene provides an additional tool to facilitate the elucidation of the molecular mechanisms underlying PCD in plants in general and in monocots in particular, because the defense response involving PCD is less understood in monocots compared with the mechanisms in dicots (Matin et al 2010). Although more than 55 rice lesion mutants were characterized in rice (Feng et al 2013), only a few of the corresponding genes have been cloned to date. About 8 genes associated with LMMs have been isolated in rice using different cloning strategies (Yamanouchi et al 2002;Zeng et al 2004;Wang et al 2005;Mori et al 2007;Takahashi et al 2007;Qiao et al 2010;Sun et al 2011), and cloning of the LESION MIMIC AND SENESCENCE (LMS) gene B encoding a protein with two double-stranded RNA binding motifs has been reported recently (Undan et al 2012).…”
Section: Discussionmentioning
confidence: 98%
“…We believe that the identification of the rice lmr mutant and isolation of the corresponding LMR gene provides an additional tool to facilitate the elucidation of the molecular mechanisms underlying PCD in plants in general and in monocots in particular, because the defense response involving PCD is less understood in monocots compared with the mechanisms in dicots (Matin et al 2010). Although more than 55 rice lesion mutants were characterized in rice (Feng et al 2013), only a few of the corresponding genes have been cloned to date. About 8 genes associated with LMMs have been isolated in rice using different cloning strategies (Yamanouchi et al 2002;Zeng et al 2004;Wang et al 2005;Mori et al 2007;Takahashi et al 2007;Qiao et al 2010;Sun et al 2011), and cloning of the LESION MIMIC AND SENESCENCE (LMS) gene B encoding a protein with two double-stranded RNA binding motifs has been reported recently (Undan et al 2012).…”
Section: Discussionmentioning
confidence: 98%
“…Primers for qRT-PCR are listed in Supplementary Table 1. PCR and detection were performed as described previously (Feng et al, 2013). The 2 −ΔΔCT method was used to analyze the relative transcript levels in gene expression with the means from three replications.…”
Section: Methodsmentioning
confidence: 99%
“…Activation of the SA response causes disease resistance to bacterial leaf blight pathogen in pelota Our previous studies have shown that rice pelota is broadly resistant to Xanthomonas oryzae pv. oryzae (Xoo), the causal pathogen of bacterial leaf blight in rice (Feng et al 2013). Although resistance to Xoo is highly associated with the spotted-leaf phenotype and a couple of defense genes were found to be upregulated in pelota (Feng et al 2013), the resistance mechanism was still unclear.…”
Section: Resultsmentioning
confidence: 99%
“…The rice pelota shows impaired growth, spotted‐leaf, and broad‐spectrum resistance to Xanthomonas oryzae pv. oryzae (Feng et al ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation